Gut Microbiome and Metabolome Changes in Mice With Acute Vestibular Deficit - Li, Feitian; Feng, Yisi; Liu, Hongyan; Kong, Dedi; Hsueh, Chi-Yao; Shi, Xunbei; Wu, Qianru; Li, Wei; Wang, Jing; Zhang, Yibo; Dai, Chunfu (Frontiers in Cellular and Infection Microbiology, 2022)
In clinical practice, the vestibular deficit is a common disorder characterized by vertigo, spontaneous nystagmus, and autonomic nervous symptoms, including nausea, vomiting, and sweating. In addition, the comorbidity of vestibular deficit and anxiety has been an integral component of the medical literature since antiquity. Previous studies suggested that the mechanism underlying the comorbidity was overlapping of vestibular and cerebellar networks. The most recent evidence showed that the microbiota-gut-brain axis plays a key role in the regulation of affective disorders. Thus, gut microbiota may be involved in vestibular deficit and anxiety comorbidity. To study this hypothesis, we built a mouse model undergoing unilateral labyrinthectomy to imitate vestibular deficit patient. 16S rRNA gene sequencing and liquid chromatography-mass spectrometry (LC-MS) were used to analyze the microbiome and metabolome of the caecal samples collected from mice in the unilateral labyrinthectomy, sham surgery and control group. Notably, unilateral labyrinthectomy shaped the composition of mice gut microbiome, resulting in more abundant Lachnospiraceae NK4A136 group, Odoribacter and Roseburia, less abundant Prevotella and Parasutterella at the genus level. The Tax4Fun functional prediction indicated lower tryptophan metabolism in unilateral labyrinthectomy mice. The functional correlation of changes in gut microbes and metabolites between different groups showed that oleamide levels negatively correlate with Odoribacter (r = -0.89, p-value = 0.0002), butyric acid positively correlate with Parasutterella (r = 0.85, p = 0.0010), propanoate negatively correlate with Prevotella (r = -0.81, p = 0.0020). Moreover, 20-HETE was positively correlated with Parasutterella (r = 0.836, p-value = 0.00133). The altered microbes and metabolites were closely related to the pathogenesis of affective disorders. The results of this study not only provide novel insights into the understanding of vestibular deficit comorbid anxiety but also build an important basis for future research on this etiology.